Effects of cooked molasses blocks on intake and digestion by steers fed brome hay with or without alfalfa - J.W. Ringler; R.H. Greenwood; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1999)
This study was conducted to determine how cattle fed medium to high quality forages respond to supplementation with cooked molasses blocks. Responses to blocks were measured for steers fed each of three different hays ad libitum: 1) brome containing 8.4% CP and 72% NDF, 2) alfalfa containing 19.2% CP and 52% NDF, and 3) brome fed ad lib and supplemented daily with 5 lb/day of the alfalfa (MIX). Eighteen steers (622 lb) were used for two periods. Six steers received each of the forages, and each steer was supplemented with the block in only one of the two periods. Blocks were fed once daily and removed after the appropriate amount had been consumed. Block intakes averaged .66 lb of dry matter daily (.55 lb OM) and were similar among forages. Forage organic matter (OM) intake was not affected by the block when brome (9.8 lb/day) or MIX (11.6 lb/day) was fed, but it decreased from 15.4 to 14.4 lb/day when the block was supplemented to alfalfa. Digestibility of OM was greater (P<.05) for alfalfa (61.0%) than brome (55.7%) or MIX (57.5%) and was not impacted by block supplementation. Digestible OM intake was greater (P<.05) for alfalfa (9.3 lb/day) than brome (5.6 lb/day) or MIX (6.8 lb/day) and was not greatly impacted by block supplementation. Thus, supplementation with a cooked molasses-urea block had only small effects on intake and digestion of medium to high quality forages.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Steers; Forage; Supplementation